Adaptive Case Managment In The System Of Medical And Social Care Of Young Persons With Adjustment Disorder, Who Use Psychoactive Substances - KiosevaЕ. V. (Psychiatry, Neurology and Medical Psychology, 2016)
The work is devoted to an actual problem– the timely implementation of the health and social care for young people with adjustment disorder, who use psychoactive substances, through an interactive intensive training on case-method, the CBL (Case Based Learning – based on clinical case), with integrated neurolinguistic technology (NLP) – «reframing». The study was conducted among 1076 students of the first years. By analyzing and modeling cases, young people acquire skills of their social, personal adaptation mechanisms; skills of increasing the level of information, cognitive, communicative, behavioral competencies, they need to implement the strategy of a healthy lifestyle.